Cold stress and acclimation - what is important for metabolic adjustment? - Janská, A; Marsík, P; Zelenková, S; Ovesná, J (Plant biology (Stuttgart, Germany), 2010)
As sessile organisms, plants are unable to escape from the many abiotic and biotic factors that cause a departure from optimal conditions of growth and development. Low temperature represents one of the most harmful abiotic stresses affecting temperate plants. These species have adapted to seasonal variations in temperature by adjusting their metabolism during autumn, increasing their content of a range of cryo-protective compounds to maximise their cold tolerance. Some of these molecules are synthesised de novo. The down-regulation of some gene products represents an additional important regulatory mechanism. Ways in which plants cope with cold stress are described, and the current state of the art with respect to both the model plant Arabidopsis thaliana and crop plants in the area of gene expression and metabolic pathways during low-temperature stress are discussed.
Keywords: rostlinné proteiny; fyziologický stres; Stress, Physiological; Plant Proteins; Signal Transduction; Arabidopsis; Acclimatization; signální transdukce; nízká teplota; aklimatizace; zemědělské plodiny; transkripční faktory; regulace genové exprese u rostlin; Transcription Factors; Gene Expression Regulation, Plant; Crops, Agricultural; Cold Temperature